The status of Her2 amplification and Kras mutations in mucinous ovarian carcinoma. Issue 1 (December 2016) - Chang, Kuang-Leei; Lee, Ming-Yung; Chao, Wan-Ru; Han, Chih-Ping
Abstract Jayson GC et al. remarked inLancet that nearly 100% of mucinous ovarian cancer cases haveKras mutation as well as a high frequency ofHer2 amplification. Using the Abbott PathVysionHer2 DNA Probe Kit andKras mutant-enriched PCR Kits (FemtoPath®), 21 samples of primary ovarian mucinous cystadenocarcinomas from Taiwanese patients were examined to determine the status ofHer2 amplification andKras mutations. Our results showed theHer2 amplification rates were 33.33%, while theKras mutation rates were 61.90%. We present here our results in order to enlighten the readership that the 100%Kras mutant frequency and the highHer2 amplification rate reported by Jayson et al. may be too exaggerated to be applicable into all populations. Additionally, we report another 2 novelKras mutations (A11V, V14I).